Biological nitrogen fixation in three wild species of the genus Lupinus (Leguminosae, Papilionoideae) in Mexico - Zamora Natera, Juan Francisco; Zapata Hernández, Isidro; Villalvazo Hernández, Alejandra (Instituto de Ecología, A.C., 2019)
Background and Aims: The biological fixation of nitrogen (BFN) in legumes native to Mexico has been little studied; particularly in species of the genus Lupinus there is no information about this. Therefore, the objective of this investigation was to evaluate the BFN in three wild lupins from the state of Jalisco, Mexico (Lupinus exaltatus, L. rotundiflorus and L. mexicanus) in terms of the amount of N fixed (kg ha-1) and the N proportion derived from the atmosphere (% Ndfa).Methods: The species under study as well as barley, a non-fixing species of N used as reference, were planted in agricultural soils in Zapopan, Jalisco, in the 2015-2016 autumn-winter season. During the growth of the species under study, destructive sampling was carried out at 93, 108 and 122 days after sowing (Das). In each sample the number of nodules per plant, dry matter content (Dm) and % N were quantified. With these values, the proportion of N derived from the atmosphere (% Ndfa) and amount of N fixed (kg ha-1) were estimated using the total N difference method.Key results: At 93, 108 and 122 Das L. exaltatus fixed 87.4, 86.9 and 187 kg of N ha-1; these values were equivalent to 71.0, 70.9 and 83.8% of Ndfa, respectively. The species L. rotundiflorus and L. mexicanus only showed significant values of N fixed until 122 Das.Conclusions: Under the conditions of this study it can be concluded that L. exaltatus was the most efficient species in the fixation of atmospheric N, due to a favorable symbiosis between the roots and the soil-fixing native bacteria of atmospheric N.